Anti-leprosy drug Clofazimine binds to human Raf1 kinase inhibitory protein and enhances ERK phosphorylation. (22nd August 2018) - Guo, Chenyun; Chang, Ting; Sun, Tao; Wu, Zhihua; Dai, Yazhuang; Yao, Hongwei; Lin, Donghai
Abstract: Human Raf1 kinase inhibitory protein (hRKIP) is an important modulator of the Ras/Raf1/MEK/ERK signaling pathway. Here, we demonstrated that anti-leprosy drug Clofazimine can bind to hRKIP with a significantly stronger affinity than the endogenous substrate phosphatidylethanolamine (PE) by using Biolayer interference technology. Moreover, we identified that residues P74, S75, K80, P111, P112, V177, and P178 play crucial roles in the binding of hRKIP to Clofazimine by using a combination of Nuclear Magnetic Resonance spectroscopy and molecular docking approach. These residues are located at the conserved ligand-binding pocket of hRKIP. Furthermore, we found that 3.2 μM Clofazimine could significantly increase the ERK phosphorylation level by about 37%. Our results indicate that Clofazimine can enhance Ras/Raf1/MEK/ERK signaling transduction pathway via binding to hRKIP. This work provides valuable hints for exploiting Clofazimine as a potential lead compound to efficiently treat the diseases related to RKIP or the Ras/Raf/MEK/ERK pathway.